Clathrin-dependent localization of alpha 1,3 mannosyltransferase to the Golgi complex of Saccharomyces cerevisiae (The Rockefeller University Press, 1994)
Posttranslational modification of yeast glycoproteins with alpha 1,3- linked mannose is initiated within a Golgi compartment analogous to the medial Golgi cisternae of higher eukaryotes. We have characterized the synthesis, posttranslational modification, and localization of the yeast alpha 1,3 mannosyltransferase (Mnn1p) using antibodies prepared against a segment of this protein expressed in bacteria. Mnn1p is initially synthesized as a 98.5-kD, type II integral membrane glycoprotein that is modified with both N- and O-linked oligosaccharides. It is subject to a slow, incremental increase in molecular mass that is dependent upon protein transport to the Golgi complex. Self-modification of Mnn1p with alpha 1,3 mannose epitopes, primarily on O-linked oligosaccharides, is at least partly responsible for the incremental increase in molecular mass. Mnn1p is a resident protein of the Golgi complex and colocalizes with guanosine diphosphatase to at least two physically distinct Golgi compartments by sucrose gradient fractionation, one of which may be a late Golgi compartment that also contains the Kex2 endopeptidase. Surprisingly, we found that a significant fraction of Mnn1p is mislocalized to the plasma membrane in a clathrin heavy chain temperature sensitive mutant while guanosine diphosphatase remains intracellular. A mutant Mnn1p that lacks the NH2-terminal cytoplasmic tail is properly localized to the Golgi complex, indicating that clathrin does not mediate Mnnlp Golgi retention by a direct interaction with the Mnn1p cytoplasmic tail. These results indicate that clathrin plays a broader role in the localization of Golgi proteins than anticipated.